A carbon electrode additive, a carbon electrode slurry, and a preparation method and application thereof
By using carbon electrode additives with specific structures in the carbon electrode to form a fluorinated alkane self-assembly layer, the problems of low work function and energy level mismatch in hole-free printable mesoscopic solar cells are solved, and the effect of improving the performance of solar cells is achieved.
Patent Information
- Application Number
- CN202211383904.8
- Authority / Receiving Office
- CN · China
- Patent Type
- Patents(China)
- Current Assignee / Owner
- Filing Date
- 2022-11-07
- Publication Date
- 2025-04-11
- Estimated Expiration
- 2042-11-07
AI Technical Summary
The low work function of the carbon electrode in the hole-free printable mesoscopic solar cell results in a large energy level mismatch with the perovskite layer, limiting the open circuit voltage and performance of the device.
A carbon electrode additive is used, with a structure of R-CF2-n, R is an alkyl group with 1-3 carbon atoms, n is a number of repeating units with -CF2-, and is an integer, 0≤n≤5. This additive forms a fluorinated alkane self-assembly layer on the surface of carbon black or graphite, and forms a surface dipole through carbon-fluorine bonds to improve the work function of the carbon electrode.
The work function of the carbon electrode is effectively improved, and the energy level can reach more than 5.3eV, solving the problem of mismatch between the energy level of the carbon electrode and the perovskite layer, and improving the photoelectric conversion efficiency and stability of solar cells.
Smart Images

Figure CN115768225B_ABST
Abstract
Description
Technical Field
[0001] The invention relates to the technical field of solar cell preparation, and in particular to a carbon electrode additive, a carbon electrode slurry, and a preparation method and application thereof. Background Art
[0002] Compared with conventional perovskite solar cells, hole-free printable mesoscopic solar cells do not have a hole transport layer, and the perovskite light-absorbing layer is in direct contact with the carbon electrode. Hole-free mesoscopic solar cells have the advantages of simple preparation process, low cost, large-scale production and excellent stability.
[0003] At present, the mesoporous carbon electrode slurry in hole-free mesoscopic solar cells mainly includes conductive graphite, conductive carbon black, zirconium dioxide high-temperature binder and cellulose as binder and pore-forming agent, and the work function of the resulting carbon electrode is usually 5.0eV. However, the valence bands of iodine lead methylamine (MAPbI3) perovskite and iodine lead formamidine (FAPbI3) perovskite are 5.4eV and 5.7eV, respectively. Therefore, there is an energy level mismatch problem between the carbon electrode and the perovskite layer, which leads to an increase in non-radiative recombination of carriers, limiting the open circuit voltage and device performance of the device.
[0004] In view of this, it is urgent to propose a mesoporous carbon electrode with high work function to further improve the performance of hole-free printable mesoscopic solar cells. Summary of the invention
[0005] The technical problem to be solved by the present invention is to provide a carbon electrode additive, a carbon electrode slurry and a preparation method and application thereof, so as to solve the technical problems in the prior art that the carbon electrode work function of hole-free printable mesoscopic solar cells is low and there is a large energy level mismatch between the carbon electrode and the perovskite layer.
[0006] In order to solve the above technical problems, the technical solution of the present invention is as follows:
[0007] A carbon electrode additive having a structure as shown in formula (I):
[0008]
[0009] Wherein, R is an alkyl group having 1 to 3 carbon atoms; n is the number of repeating units of -CF2-, which is an integer, and 0≤n≤5.
[0010] The invention also provides a carbon electrode slurry containing the carbon electrode additive.
[0011] Preferably, the carbon electrode slurry further comprises conductive graphite, conductive carbon black, a binder, a pore former and a solvent.
[0012] Preferably, the conductive graphite is one or more of graphite or functionalized graphite;
[0013] Wherein, the functionalized graphite is fluorinated graphite.
[0014] Optionally, the conductive carbon black is one or more of carbon black or functionalized carbon black;
[0015] Wherein, the functionalized carbon black is nitrided carbon black.
[0016] Optionally, the binder is zirconium dioxide;
[0017] Optionally, the pore former is ethyl cellulose;
[0018] Optionally, the solvent is one or more of ethanol or terpineol.
[0019] Preferably, the weight ratio of the carbon electrode additive to the sum of the mass of the conductive graphite and the conductive carbon black is (0.1-10):100.
[0020] Preferably, the carbon electrode slurry comprises the following raw materials in parts by weight:
[0021]
[0022] The present invention also provides a method for preparing the carbon electrode slurry, comprising the following steps:
[0023] Conductive graphite, conductive carbon black, a binder, a pore former, and a solvent are mixed evenly, and a carbon electrode additive is added to the mixture and mixed evenly to obtain a carbon electrode slurry.
[0024] Preferably, the method for preparing the carbon electrode slurry specifically comprises the following steps:
[0025] Conductive graphite, conductive carbon black, binder, pore former and solvent are mixed evenly, a carbon electrode additive is added to the mixture, and ball milling or sand milling is performed to mix evenly, and then the solvent is removed and ground to obtain a carbon electrode slurry.
[0026] More preferably, the solvent is removed by a rotary evaporator. The grinding is performed by a three-roll mill.
[0027] Preferably, the method for preparing the carbon electrode slurry further comprises the step of adding water or acid after adding the carbon electrode additive.
[0028] Further preferably, the mass ratio of the water or acid to the carbon electrode additive is (0.1-2):1.
[0029] The present invention also provides an application of the carbon electrode slurry in preparing carbon electrodes in mesoscopic solar cells.
[0030] Preferably, the carbon electrode slurry is prepared into a carbon electrode by scraping or screen printing.
[0031] The invention also provides a mesoscopic solar cell, comprising a carbon electrode prepared from the carbon electrode slurry.
[0032] The above solution of the present invention includes at least the following beneficial effects:
[0033] (1) The carbon electrode additive of the present invention has a structure as shown in formula (I). The carbon electrode additive with a structure as shown in formula (I) can be hydrolyzed, and its hydrolysis product is a fluorinated silanol with a structure as shown in formula (II) or a fluorinated siloxane polycondensate with a structure as shown in formula (III), specifically as follows:
[0034]
[0035] Wherein, the fluorinated siloxane polycondensate is formed by continued dehydration condensation of fluorinated silanol.
[0036] The above hydrolysis products can form a fluorinated alkane self-assembly layer on the surface of carbon black or graphite, and can effectively improve the work function of the carbon electrode by forming a surface dipole effect through the carbon-fluorine bond, and the energy level can reach a work function greater than 5.3eV, that is, there is no energy level problem, which solves the energy level mismatch problem between the carbon electrode and the perovskite layer in the hole-free printable mesoscopic solar cell, and achieves the technical effect of improving the performance of the solar cell. In addition, the carbon-fluorine bond has high hydrophobicity, which is conducive to improving the hydrophobicity of the carbon electrode to improve the performance and stability of the battery.
[0037] (2) The carbon electrode slurry of the present invention can be used to produce carbon electrodes on a large scale by means of scraping, coating, screen printing, etc., with simple process and low cost. BRIEF DESCRIPTION OF THE DRAWINGS
[0038] Figure 1 It is a current-voltage curve diagram of the mesoscopic solar cell prepared in Example 1 of the present invention and Comparative Example 1. DETAILED DESCRIPTION
[0039] The exemplary embodiments of the present disclosure will be described in more detail below with reference to the accompanying drawings. Although the exemplary embodiments of the present disclosure are shown in the accompanying drawings, it should be understood that the present disclosure can be implemented in various forms and should not be limited by the embodiments set forth herein. On the contrary, these embodiments are provided to enable a more thorough understanding of the present disclosure and to fully convey the scope of the present disclosure to those skilled in the art.
[0040] Example 1
[0041] The carbon electrode additive of this embodiment has a structure as shown in formula (I):
[0042]
[0043] Wherein, R is an alkyl group with 2 carbon atoms; n is the number of repeating units of -CF2-, which is equal to 5. That is, the carbon electrode additive is 1H,1H,2H,2H-perfluorooctyltriethoxysilane, and its chemical formula is as follows:
[0044]
[0045] The CAS number of the 1H,1H,2H,2H-perfluorooctyltriethoxysilane is 51851-37-7, which can be obtained by purchasing a commercial product or prepared by itself. In this embodiment, the 1H,1H,2H,2H-perfluorooctyltriethoxysilane was purchased from Nanjing Nengde New Material Technology Co., Ltd.
[0046] The carbon electrode slurry of this embodiment contains the above-mentioned carbon electrode additive. The carbon electrode slurry also includes conductive graphite, conductive carbon black, a binder, a pore former, and a solvent. Among them, the conductive graphite is pure graphite; the conductive carbon black is pure carbon black; the binder is zirconium dioxide; the pore former is ethyl cellulose; and the solvent is ethanol.
[0047] The carbon electrode slurry specifically comprises the following raw materials in parts by weight:
[0048]
[0049] The weight ratio of the carbon electrode additive to the sum of the mass of the conductive graphite and the conductive carbon black is 0.1:18.
[0050] The method for preparing the carbon electrode slurry of this embodiment comprises the following steps:
[0051] Conductive graphite, conductive carbon black, binder, pore former and solvent are mixed evenly, carbon electrode additive and water are added to the mixture, and ball milling or sand milling is performed to mix evenly, and then the solvent is removed by rotary evaporation equipment, and a three-roll mill is used for grinding to obtain carbon electrode slurry.
[0052] Wherein, the mass ratio of the water to the carbon electrode additive is 0.1:1.
[0053] The carbon electrode slurry described in this embodiment is used to prepare the carbon electrode in the mesoscopic solar cell. The carbon electrode slurry is made into the carbon electrode by screen printing, which specifically includes the following steps:
[0054] The carbon electrode slurry is made into a thin film by screen printing, and then sintered at 400° C. for 1 hour to obtain a carbon electrode.
[0055] It should be noted that the carbon electrode slurry can also be replaced by a method of scraping or coating to form a carbon electrode. In addition, those skilled in the art can adjust the thickness of the carbon electrode by changing the solid content of the slurry or the mesh size of the printing screen, and the thickness can be any value within the range of 5-50 microns. In this embodiment, the thickness of the prepared carbon electrode is 50 microns.
[0056] The mesoscopic solar cell of this embodiment includes the carbon electrode, and its structure is FTO / c-TiO2 / m-TiO2 / ZrO2 / perovskite / C; wherein FTO is fluorine-doped SnO2 conductive glass, c-TiO2 is a dense titanium dioxide layer, m-TiO2 is a mesoporous titanium dioxide layer, ZrO2 is a mesoporous insulating layer, and C is a carbon electrode. The preparation method of the mesoscopic solar cell is as follows:
[0057] A dense titanium dioxide layer c-TiO2 is sprayed on the FTO conductive glass, a mesoporous titanium dioxide layer m-TiO2 is prepared by screen printing, a mesoporous insulating layer ZrO2 is prepared by screen printing, a carbon electrode is prepared by screen printing, and finally, iodine lead methylamine perovskite solution MAPbI3 is dripped onto the surface of the carbon electrode and dried to obtain a mesoscopic solar cell.
[0058] Example 2
[0059] The carbon electrode additive of this embodiment has a structure as shown in formula (I):
[0060]
[0061] Wherein, R is an alkyl group with a carbon atom number of 1; n is the number of repeating units of -CF2-, which is equal to 0. That is, the carbon electrode additive is 3,3,3-trifluoropropyltrimethoxysilane, and its chemical formula is as follows:
[0062]
[0063] The 3,3,3-trifluoropropyltrimethoxysilane can be obtained by purchasing a commercial product or can be prepared by itself. In this embodiment, the 3,3,3-trifluoropropyltrimethoxysilane was purchased from Nanjing Nengde New Material Technology Co., Ltd.
[0064] The carbon electrode slurry of this embodiment contains the above-mentioned carbon electrode additive. The carbon electrode slurry also includes conductive graphite, conductive carbon black, a binder, a pore former, and a solvent. Among them, the conductive graphite is functionalized graphite, i.e., graphite fluoride; the conductive carbon black is functionalized carbon black, i.e., nitrided carbon black; the binder is zirconium dioxide; the pore former is ethyl cellulose; and the solvent is pine alcohol.
[0065] The carbon electrode slurry specifically comprises the following raw materials in parts by weight:
[0066]
[0067] The weight ratio of the carbon electrode additive to the sum of the mass of the conductive graphite and the conductive carbon black is 1:20.
[0068] The method for preparing the carbon electrode slurry of this embodiment comprises the following steps:
[0069] Conductive graphite, conductive carbon black, binder, pore former and solvent are mixed evenly, carbon electrode additive and hydrochloric acid are added to the mixture, and ball milling or sand milling is performed to mix evenly, and then the solvent is removed by rotary evaporation equipment, and a three-roll mill is used for grinding to obtain carbon electrode slurry.
[0070] The mass ratio of the hydrochloric acid to the carbon electrode additive is 1:1. The concentration of the hydrochloric acid is 1 mol / lL.
[0071] The carbon electrode slurry described in this embodiment is used to prepare the carbon electrode in the mesoscopic solar cell. The carbon electrode slurry is made into the carbon electrode by screen printing, which specifically includes the following steps:
[0072] The carbon electrode slurry is made into a thin film by screen printing, and then sintered at 400° C. for 1 hour to obtain a carbon electrode.
[0073] It should be noted that the carbon electrode slurry can also be replaced by a method of scraping or coating to form a carbon electrode. In addition, those skilled in the art can adjust the thickness of the carbon electrode by changing the solid content of the slurry or the mesh size of the printing screen, and the thickness can be any value within the range of 5-50 microns. In this embodiment, the thickness of the prepared carbon electrode is 50 microns.
[0074] The mesoscopic solar cell of this embodiment has the same structure as that of Embodiment 1 and is prepared by the same method.
[0075] Example 3
[0076] The carbon electrode additive of this embodiment has a structure as shown in formula (I):
[0077]
[0078] Wherein, R is an alkyl group with 3 carbon atoms; n is the number of repeating units of -CF2-, which is equal to 3. That is, the carbon electrode additive is 1H,1H,2H,2H-perfluorohexyltripropoxysilane, and its chemical formula is as follows:
[0079]
[0080] The 1H,1H,2H,2H-perfluorohexyltripropoxysilane can be obtained by purchasing a commercial product or prepared by itself.
[0081] The carbon electrode slurry of this embodiment contains the above-mentioned carbon electrode additive. The carbon electrode slurry also includes conductive graphite, conductive carbon black, a binder, a pore former, and a solvent. Among them, the conductive graphite is pure graphite; the conductive carbon black is pure carbon black; the binder is zirconium dioxide; the pore former is ethyl cellulose; and the solvent is a mixture of ethanol and pine alcohol in a weight ratio of 1:3.
[0082] The carbon electrode slurry specifically comprises the following raw materials in parts by weight:
[0083]
[0084] The weight ratio of the carbon electrode additive to the sum of the mass of the conductive graphite and the conductive carbon black is 0.5:16.
[0085] The method for preparing the carbon electrode slurry of this embodiment comprises the following steps:
[0086] Conductive graphite, conductive carbon black, binder, pore former and solvent are mixed evenly, carbon electrode additive and water are added to the mixture, and ball milling or sand milling is performed to mix evenly, and then the solvent is removed by rotary evaporation equipment, and a three-roll mill is used for grinding to obtain carbon electrode slurry.
[0087] Wherein, the mass ratio of the water to the carbon electrode additive is 2:1.
[0088] The carbon electrode slurry described in this embodiment is used to prepare the carbon electrode in the mesoscopic solar cell. The carbon electrode slurry is made into the carbon electrode by screen printing, which specifically includes the following steps:
[0089] The carbon electrode slurry is made into a thin film by screen printing, and then sintered at 400° C. for 1 hour to obtain a carbon electrode.
[0090] It should be noted that those skilled in the art can adjust the thickness of the carbon electrode by changing the solid content of the slurry or the mesh size of the printing screen, and the thickness can be any value within the range of 5-50 microns. In this embodiment, the thickness of the prepared carbon electrode is 50 microns.
[0091] The mesoscopic solar cell of this embodiment has the same structure as that of Embodiment 1 and is prepared by the same method.
[0092] Example 4
[0093] The carbon electrode additive of this embodiment has a structure as shown in formula (I):
[0094]
[0095] Wherein, R is an alkyl group with 2 carbon atoms; n is the number of repeating units of -CF2-, which is equal to 5. That is, the carbon electrode additive is 1H,1H,2H,2H-perfluorooctyltriethoxysilane, and its chemical formula is as follows:
[0096]
[0097] The CAS number of the 1H,1H,2H,2H-perfluorooctyltriethoxysilane is 51851-37-7, which can be obtained by purchasing a commercial product or prepared by itself. In this embodiment, the 1H,1H,2H,2H-perfluorooctyltriethoxysilane was purchased from Nanjing Nengde New Material Technology Co., Ltd.
[0098] The carbon electrode slurry of this embodiment contains the above-mentioned carbon electrode additive. The carbon electrode slurry also includes conductive graphite, conductive carbon black, a binder, a pore former, and a solvent. Among them, the conductive graphite is pure graphite; the conductive carbon black is pure carbon black; the binder is zirconium dioxide; the pore former is ethyl cellulose; and the solvent is ethanol.
[0099] The carbon electrode slurry specifically comprises the following raw materials in parts by weight:
[0100]
[0101] The weight ratio of the carbon electrode additive to the sum of the mass of the conductive graphite and the conductive carbon black is 1:18.
[0102] The method for preparing the carbon electrode slurry of this embodiment comprises the following steps:
[0103] Conductive graphite, conductive carbon black, binder, pore former and solvent are mixed evenly, carbon electrode additive and water are added to the mixture, and ball milling or sand milling is performed to mix evenly, and then the solvent is removed by rotary evaporation equipment, and a three-roll mill is used for grinding to obtain carbon electrode slurry.
[0104] Wherein, the mass ratio of the water to the carbon electrode additive is 0.1:1.
[0105] The carbon electrode slurry described in this embodiment is used to prepare the carbon electrode in the mesoscopic solar cell. The carbon electrode slurry is made into the carbon electrode by screen printing, which specifically includes the following steps:
[0106] The carbon electrode slurry is made into a thin film by screen printing, and then sintered at 400° C. for 1 hour to obtain a carbon electrode.
[0107] It should be noted that the carbon electrode slurry can also be replaced by a method of scraping or coating to form a carbon electrode. In addition, those skilled in the art can adjust the thickness of the carbon electrode by changing the solid content of the slurry or the mesh size of the printing screen, and the thickness can be any value within the range of 5-50 microns. In this embodiment, the thickness of the prepared carbon electrode is 50 microns.
[0108] The mesoscopic solar cell of this embodiment has the same structure as that of Embodiment 1 and is prepared by the same method.
[0109] Example 5
[0110] This embodiment uses the same carbon electrode additive as that of Embodiment 4, with the only difference being that the weight fraction of the carbon electrode additive in the carbon electrode slurry is replaced with 0.01 parts.
[0111] Comparative Example 1
[0112] The carbon electrode slurry of this comparative example is the same as that of Example 4, except that it does not include a carbon electrode additive.
[0113] The carbon electrode slurry of this comparative example was prepared by the same preparation method as that of Example 4, and the mesoscopic solar cell was prepared by the same method as that of Example 4.
[0114] Effect comparison ratio
[0115] In order to verify the technical effect of the carbon electrode additive described in the present invention, the following experiments were conducted:
[0116] The carbon electrodes prepared in Examples 1-5 and Comparative Example 1 were tested for resistance using a four-probe and for work function using a Kelvin probe.
[0117] The mesoscopic solar cells prepared in Examples 1-5 and Comparative Example 1 were subjected to a standard sunlight intensity (AM 1.5G, 100 mW / cm 2 ) to test open circuit voltage, current density, fill factor, and photoelectric conversion efficiency. Figure 1 Shown is a current-voltage curve diagram of the mesoscopic solar cell prepared in Example 1 and Comparative Example 1.
[0118] After experimentation, the results are as follows:
[0119]
[0120]
[0121] According to the comparison between Examples 1-5 and Comparative Example 1, the carbon electrode additive of the present invention can effectively improve the work function of the carbon electrode, and the energy level can reach a work function greater than 5.3 eV, which solves the energy level mismatch problem between the carbon electrode and the perovskite layer in the hole-free printable mesoscopic solar cell, and greatly improves the photoelectric conversion efficiency. According to the comparison between Example 4 and Example 5, when the amount of the carbon electrode additive in the carbon electrode slurry is too small, it cannot play a significant role in improving the work function of the carbon electrode, and the improvement of the photoelectric conversion efficiency is also limited.
[0122] The above is a preferred embodiment of the present invention. It should be pointed out that for ordinary technicians in this technical field, several improvements and modifications can be made without departing from the principles of the present invention. These improvements and modifications should also be regarded as the scope of protection of the present invention.
Claims
1. A carbon electrode additive, characterized in that: It has a structure as shown in formula (I): (Ⅰ) Wherein, R is an alkyl group having 1 to 3 carbon atoms; n is the number of repeating units of -CF2-, which is an integer, and 0≤n≤5.
2. A carbon electrode slurry, characterized in that: Contains the carbon electrode additive according to claim 1.
3. The carbon electrode slurry according to claim 2, characterized in that: It also includes conductive graphite, conductive carbon black, a binder, a pore former, and a solvent.
4. The carbon electrode slurry according to claim 3, characterized in that The conductive graphite is one or more of graphite or functionalized graphite; The conductive carbon black is one or more of carbon black or functionalized carbon black; The binder is zirconium dioxide; The pore-forming agent is ethyl cellulose; The solvent is one or more of ethanol or terpineol.
5. The carbon electrode slurry according to claim 3, characterized in that: The weight ratio of the carbon electrode additive to the sum of the mass of the conductive graphite and the conductive carbon black is (0.1-10):
100.
6. The carbon electrode slurry according to claim 3, characterized in that: The invention comprises the following raw materials in parts by weight: Carbon electrode additive 0.1-1 part; Conductive graphite 10-18 parts; Conductive carbon black 2-6 parts; 1-6 parts of adhesive; 1-5 parts of pore-forming agent; 40-60 parts of solvent.
7. A method for preparing a carbon electrode slurry according to any one of claims 2 to 6, characterized in that: The steps include: Conductive graphite, conductive carbon black, a binder, a pore former, and a solvent are mixed evenly, and a carbon electrode additive is added to the mixture and mixed evenly to obtain a carbon electrode slurry.
8. The method for preparing the carbon electrode slurry according to claim 7, characterized in that: The specific steps include: Conductive graphite, conductive carbon black, binder, pore former and solvent are mixed evenly, a carbon electrode additive is added to the mixture, and ball milling or sand milling is performed to mix evenly, and then the solvent is removed and ground to obtain a carbon electrode slurry.
9. Use of the carbon electrode slurry according to any one of claims 2 to 6 in preparing carbon electrodes for mesoscopic solar cells.
10. A mesoscopic solar cell, characterized in that: A carbon electrode prepared from the carbon electrode slurry according to any one of claims 2 to 6.
Citation Information
Patent Citations
Perovskite solar cell and carbon slurry and preparation method thereof
CN115064301A
Carbon paste composite of conducting carbon nano tubeand making method of flexible film type Inorganicelectroluminescence device using of
KR1020050037180A